Changes in the carbon balance of tropical forests: Evidence from long- term plots - Phillips, Oliver L.; Malhi, Yadvinder Singh; Higuchi, Niro; Laurance, William F.; Núñez, Percy V.; Vásquez, Rodolfo V.; Laurance, Susan G.W.; Ferreira, Leandro Valle; Stern, Margaret J.; Brown, Sandra L.; Grace, John (Science, 1998)
The role of the world's forests as a 'sink' for atmospheric carbon dioxide is the subject of active debate. Long-term monitoring of plots in mature humid tropical forests concentrated in South America revealed that biomass gain by tree growth exceeded losses from tree death in 38 of 50 Neotropical sites. These forest plots have accumulated 0.71 ton, plus or minus 0.34 ton, of carbon per hectare per year in recent decades. The data suggest that Neotropical forests may be a significant carbon sink, reducing the rate of increase in atmospheric carbon dioxide.
Keywords: Atmospheric Carbon Dioxide; Tropical Forests; Biomass; Carbon Dioxide; Forestry; Measurement Errors; Plants (botany); Ecosystems; Carbon; Carbon Dioxide; Atmospheric Sink; Biogeochemical Cycle; Carbon Budget; Community Response; Tropical Forest; Biomass; Carbon Dioxide Fixation; Death; Forest; Plant Growth; Priority Journal; Review; South America; Tree; South America